Disruption of nNOS–NOS1AP protein–protein interactions suppresses neuropathic pain in mice. Issue 5 (May 2018) - Lee, Wan-Hung; Li, Li-Li; Chawla, Aarti; Hudmon, Andy; Lai, Yvonne Y.; Courtney, Michael J.; Hohmann, Andrea G.
Abstract : Abstract: Elevated N -methyl-D-aspartate receptor (NMDAR) activity is linked to central sensitization and chronic pain. However, NMDAR antagonists display limited therapeutic potential because of their adverse side effects. Novel approaches targeting the NR2B-PSD95-nNOS complex to disrupt signaling pathways downstream of NMDARs show efficacy in preclinical pain models. Here, we evaluated the involvement of interactions between neuronal nitric oxide synthase (nNOS) and the nitric oxide synthase 1 adaptor protein (NOS1AP) in pronociceptive signaling and neuropathic pain. TAT-GESV, a peptide inhibitor of the nNOS–NOS1AP complex, disrupted the in vitro binding between nNOS and its downstream protein partner NOS1AP but not its upstream protein partner postsynaptic density 95 kDa (PSD95). Putative inactive peptides (TAT-cp4GESV and TAT-GESVΔ1) failed to do so. Only the active peptide protected primary cortical neurons from glutamate/glycine-induced excitotoxicity. TAT-GESV, administered intrathecally (i.t.), suppressed mechanical and cold allodynia induced by either the chemotherapeutic agent paclitaxel or a traumatic nerve injury induced by partial sciatic nerve ligation. TAT-GESV also blocked the paclitaxel-induced phosphorylation at Ser15 of p53, a substrate of p38 MAPK. Finally, TAT-GESV (i.t.) did not induce NMDAR-mediated motor ataxia in the rotarod test and did not alter basal nociceptive thresholds in the radiant heat tail-flick test. These observations support the hypothesis that antiallodynic efficacy of an nNOS–NOS1AP disruptor may result, at least in part, from blockade of p38 MAPK-mediated downstream effects. Our studies demonstrate, for the first time, that disrupting nNOS–NOS1AP protein–protein interactions attenuates mechanistically distinct forms of neuropathic pain without unwanted motor ataxic effects of NMDAR antagonists. Abstract : The peptide inhibitor TAT-GESV, but not an inactive analog, disrupts nNOS–NOS1AP protein–protein interactions through a direct mechanism, produces neuroprotection and suppresses neuropathic pain.